Clinical outcomes of urinary tract infection caused by extended spectrum beta‐lactamase producing Enterobacteriaceae: a retrospective observational study comparing patients with and without systemic inflammatory response syndrome. Issue 1 (5th December 2019) - Kitano, Yuka; Wakatake, Haruaki; Saito, Hiroki; Tsutsumi, Ken; Yoshida, Hideki; Yoshida, Minoru; Takita, Mumon; Yoshida, Toru; Masui, Yoshihiro; Taira, Yasuhiko; Fujitani, Shigeki
Abstract : Aim: In severe urinary tract infection (UTI), susceptible antibiotics should be given. With the recent increase of multidrug‐resistant bacteria, especially extended spectrum beta‐lactamase producing Enterobacteriaceae (ESBL‐E), broad‐spectrum antibiotics, such as carbapenems, are used more frequently, which could lead to a further increase of multidrug‐resistant bacteria. We aimed to analyze the relationship between initial empirical antibiotic appropriateness and clinical outcomes in UTI, especially in patients with systemic inflammatory response syndrome (SIRS) and ESBL‐E. Methods: A retrospective observational study from 2012 to 2017. Results: Among urine culture‐positive cases with ≥10 5 colony‐forming units/mL ( n = 1, 880), true UTI cases were extracted ( n = 844) and divided into the SIRS group ( n = 336 [ESBL‐E12.8% (43/336)]) and non‐SIRS group ( n = 508 [ESBL‐E12.6% (64/508)]). In the SIRS ESBL‐E group, the initial antibiotics were susceptible in 55.8% (24/43), among which 91.7% (22/24) improved and 8.3% (2/24) deteriorated or died. The initial antibiotics were resistant in 44.2% (19/43), among which 47.4% (9/19) improved with the initial antibiotics, 47.4% (9/19) improved after escalating antibiotics, and 5.3% (1/19) deteriorated or died. In the SIRS group, 14 cases had true bacteremia with ESBL‐E. Seven cases were initiated with inappropriate antibiotics; four cases showed improvement before or without antibiotic change and three cases improved after antibiotic escalation. Conclusion: Initiation of narrow‐spectrum antibiotics in septic UTI with ESBL‐E might not deteriorate the clinical outcome if promptly escalated on clinical deterioration or with ESBL‐E culture results. Further investigation is warranted to guide judicious use of initial antibiotics. Abstract : We undertook this study to evaluate clinical outcomes of urinary tract infection caused by extended spectrum beta‐lactamase producing Enterobacteriaceae. Our specific interest is to assess the clinical outcomes in relation to the initial empirical antibiotics, especially in severe cases.